Representasi Emosi dan Harapan pada Lirik Lagu “Terbuang dalam Waktu” Karya Barasuara Kajian Stilistika dan Retorika - Mufidah, Sarwatul (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
Song lyrics function not only as entertainment but also as a medium of communication that conveys emotional and social messages to listeners. Barasuara’s “Terbuang dalam Waktu” is particularly interesting to study because it combines the themes of grief and hope through distinctive stylistic choices, and its popularity increased significantly after being featured as the soundtrack of the film Sore: Istri dari Masa Depan, which brought the song to wider public recognition. This study aims to describe how emotions and hope are represented in the lyrics of “Terbuang dalam Waktu” by applying stylistic and rhetorical analysis. The research employed a descriptive qualitative method, with the lyric text as the primary data. The analysis focused on identifying stylistic devices such as repetition, parallelism, and metaphor, as well as rhetorical devices such as rhetorical questions, lexical reinforcement, and peroration, which were then interpreted within linguistic and communication frameworks. The findings show that the opening part of the lyrics is dominated by negative emotions such as sadness, inner wounds, and doubt, expressed through repetition, parallelism, and rhetorical questions. A turning point appears in the performative verb “berubah,” which shifts the discourse from despair to action. The closing part represents hope and love through growth metaphors, emotional support, and the statement “cinta tak kenal waktu” as the peak of the message. The combination of stylistic and rhetorical devices ensures that the song’s message is delivered powerfully and emotionally, allowing listeners not only to understand the lyrics but also to experience the journey from grief to hope.